Assessment and Diagnostics of the Development of Distributed Generation in Ukraine - Kyzym Mykola O.; Lelyuk Oleksіy V.; Kostenko Dmytro M. (Problemi Ekonomiki, 2018)
The article proves that the concept of centralized energy supply is losing its significance, and the ideology of the new paradigm of energy development, among the basic provisions of which there is the need for the advanced development of distributed energy systems, comes to replace it. The aim of the article is to develop and test a methodological approach to assessing the level of development of distributed generation in Ukraine and its regions. There defined the essence of the concept “distributed generation” and its main principles: 1 – proximity of the location of production facilities to consumers; 2 – flexibility of production facilities; 3 – use of diversified nomenclature of primary fuel and energy resources (PFER). The methodological approach to assessing the development level of distributed generation in Ukraine and its regions is proposed. Within the framework of the approach: the indicator of covering demand by local production of regions of Ukraine is calculated; the degree of adequacy of local production for covering electricity demand in them is estimated; the indicators of development of distributed generation in regions of Ukraine are calculated; the structure of the power generation park in the country is studied, and the indicator of flexibility of production facilities in its regions is calculated; the level of flexibility of facilities in regions of the country is assessed; the structure of the power generation park in Ukraine by type of PFER is analyzed, and the indicator of diversification of production facilities in regions of the country by type of PFEPs is calculated; the level of diversification of facilities in regions of Ukraine by type of PFEPs is assessed; based on individual indicators, including the indicators of covering demand by production, energy flexibility, and diversification of facilities, the integral indicator of the development level of distributed generation in regions of Ukraine in 2017 is calculated.